Preparation and characterization of fully waste-based glass-ceramics from incineration fly ash, waste glass and coal fly ash. Issue 15 (1st August 2022) - Zhang, Zhikun; Li, Zhichuan; Yang, Yibo; Shen, Boxiong; Ma, Jiao; Liu, Lina
Abstract: Municipal solid waste incineration (MSWI) fly ash (FA) is a typical hazardous waste due to its high contents of toxic heavy metals, and hence its disposal has attracted global concern. In this work, it was recycled into environmental-friendly CaO–Al2 O3 –SiO2 system glass-ceramics via adding coal fly ash (CFA) and waste glass (WG). The effects of CaO/SiO2 ratios and sintering temperatures on the crystalline phases, morphologies, mechanical and chemical properties, heavy metals leaching and potential ecological risks of glass-ceramics were investigated. The results showed that wollastonite (CaSiO3 ), anorthite (CaAl2 Si2 O8 ) and gehlenite (Ca2 Al2 SiO7 ) were the dominant crystals in the glass-ceramics, which were not affected by CaO/SiO2 ratio and sintering temperature. The compressive strength increased, while the Vickers hardness and microhardness decreased as increasing the sintering temperatures from 850 to 1050 °C, which reached their maximum values of 660.69 MPa, 6.14 GPa, and 7.43 GPa, respectively. However, the increase of CaO/SiO2 ratio resulted into the reduction of the three mechanical parameters. As varying CaO/SiO2 ratio from 0.48 to 0.86, the maximum compressive strength, Vickers hardness and microhardness were 611.80 MPa, 5.43 GPa, and 6.56 GPa, respectively. Besides, all the glass-ceramics exhibited high alkali resistance of >97%. The extremely low heavy metals leaching concentrations and low potential ecological risk of glass-ceramics further revealed its environmentally friendly property and potential application feasibility.